Comparison of Original and Modern Mortars at the Herculaneum Archaeological Site. (4th March 2019) - Leone, Gemma; De Vita, Alessandra; Consumi, Marco; Tamasi, Gabriella; Bonechi, Claudia; Donati, Alessandro; Rossi, Claudio; Magnani, Agnese
ABSTRACT: This paper aims to evaluate mineralogical, elemental, and thermal differences among original Roman joint mortars and those used in twentieth-century restoration campaigns taken from different areas at the Herculaneum archaeological site. The purpose is to improve the compatibility of restoration mortars. Roman and modern mortars were studied with petrography, thermal analysis and x-ray fluorescence investigations. The results indicate significant differences between the Roman and modern mortars which could facilitate the degradation process. Roman mortars, in particular, were composed of a coarser aggregate which was present in a lower ratio with binder in comparison with modern mortars.